2017
DOI: 10.1111/ijn.12577
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' use of mobile instant messaging applications: A uses and gratifications perspective

Abstract: In general, the results show that mobile instant messaging applications are routinely used by Filipino staff nurses not only for clinical purposes (ie, information exchange) but also for non-clinical purposes (ie, socialization and catharsis). This paper ends with several practical and theoretical implications including future research directions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…Most straightforward of the interventions offered was a text messaging service or smartphone‐based messaging app. Two studies investigated how text messaging could offer emotional and social support to nurses – one using a qualitative approach (Bautista & Lin, ) and another using mixed methodology (Boath et al, ). Bautista and Lin () set out to explore how Filipino nurses used smartphone messaging apps such as Facebook Messenger and Viber.…”
Section: Resultsmentioning
confidence: 99%
“…Most straightforward of the interventions offered was a text messaging service or smartphone‐based messaging app. Two studies investigated how text messaging could offer emotional and social support to nurses – one using a qualitative approach (Bautista & Lin, ) and another using mixed methodology (Boath et al, ). Bautista and Lin () set out to explore how Filipino nurses used smartphone messaging apps such as Facebook Messenger and Viber.…”
Section: Resultsmentioning
confidence: 99%
“…Smartphone technology is an accessible medium of communication, and online support has been used extensively by patients with beneficial effects (Doswell, Braxter, DeVito Dabbs, Nilsen, & Klem, 2013;Ganasegeran, Renganathan, Rashid, & Al-Dubai, 2017;Marin et al, 2016;O' Connor & Andrews, 2016). Findings of the literature review demonstrated that smartphone messaging was found to improve the well-being of nursing staff in the Philippines by meeting needs for socializing and providing an opportunity for catharsis (Bautista & Lin, 2017). Eight electronic databases were searched, comprised of AMED, British Nursing Index, CINAHL, EMBASE, Medline, Science Full Text, PsychINFO, and PubMed.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, social media applications like Facebook® and WhatsApp® have been used successfully as support tools in rural midwifery practice in South Africa where staff reported that it was difficult to meet in person (Chipps et al, 2015). Such egalitarian support was also identified as helpful for nurses during first year student placements (Morley, 2014) and additional papers were retrieved which detailed nurses' informal use of text messaging as social support (Bautista & Lin, 2017) and the development of a smartphone application aimed at improving social support for both students and mentors on nursing training programs in the UK (Colton & Hunt, 2016). Additional studies were retrieved on face-to-face peer support and mentoring in nursing, with both being recommended as a means to preventing nurses from quitting the profession (Nkwantabisah, Hackstaff, Paluch, & Zerwekh, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations